Desain dan Verifikasi Kontrol Cascade Pengendali Suhu Berbasis Fuzzy-PID dan PI pada Heat Exchanger - Yusuf Efendi (Universitas Negeri Padang, 2019)
In industry, in controlling heat exchanger temperature, there exist some disturbances that potentially affect the performance of the heat exchanger. One of them is the change of outside temperature. This study proposes cascade control techniques with fuzzy-PID and PI methods, respectively as primary and secondary controllers to overcome the disturbance and to result more stable performance of the system. Verification on the cascade fuzzy-PID control technique showed performance of the system was improved in term of rise time (tr), overshoot (mp), and settling time (ts). Cascade control technique played a role in handling the changes of system parameters, while the combination of fuzzy-PID overcame the interference. The combination of feedback control and cascade control techniques with fuzzy-PID method can make the performance of the system more stable and overcome the interference.